ThIRST: Targeted IRrigation Support Tool for sustainable coffee production - Nguyen, Kien Tri; Craparo, Alessandro Carmelo William; Nguyen, Phuong Minh; Turreira-García, Nerea; Talsma, Tiffany; Deniau, Aline; Bossolasco, Laurent; Le, Trung Dang; Bosselmann, Aske Skovmand (Frontiers Media, 2023)
The Central Highlands of Vietnam is an important Robusta coffee growing region. However, the region is facing climate change impacts from rising temperatures and irregular rainfall, while Vietnamese coffee farmers predominantly rely on irrigation from heavily depleted aquifers. To continue productive and sustainable growth, this system requires an innovative approach to meet this hydrological challenge. Here we propose a user-friendly tool, which aims to support coffee farmers’ irrigation decisions, through the Targeted Irrigation Support Tool or ThIRST. ThIRST combines seasonal forecasts, on-farm metrics, and farmer’s expertise. The research comprises baseline ( n = 400) and endline ( n = 237) surveys of coffee farmers in Đắk Lắk and Lâm Đồng Provinces. Through the surveys, farmers’ irrigation needs and the applicability of the tool are evaluated. Despite low smartphone usage for farming advisory, the results show the tool allows coffee farmers to continually achieve water-use efficiency and adapt to climate variability. Involving farmers in the design, production and evaluation of climate services can improve the trust and uptake of agro-advisories and the way this information is communicated.